Pendidikan Islam Inklusif Di Sekolah Dasar: Merangkul Perbedaan Dan Membangun Toleransi Di Kecamatan Paseh Kabupaten Sumedang - Alfazri, Dimas; Permana, Rifki Adit Tia; Putri, Natasya Dwi Meilany; Wijana, Wijana; Supriyadi, Tedi (Edification Journal : Pendidikan Agama Islam, 2025)
This article explores the implementation of inclusive Islamic education in elementary schools to foster a fair, open, and respectful learning environment. It highlights how Islamic stories, open discussion, and mutual respect can cultivate tolerance among students. The study employs a case study method, involving Islamic Education (PAI) teachers from five elementary schools in Paseh District, Sumedang Regency. The findings reveal the crucial role of PAI teachers in developing students' tolerance through their examples, diverse teaching strategies, and the use of varied media. Examples of inclusive practices include adjusting teaching methods, disseminating relevant materials, and creating a classroom atmosphere that considers students' diverse backgrounds. However, the research also identifies existing challenges, such as teachers lacking the skills to support students with special needs, insufficient understanding of individual differences, and inadequate collaboration between schools and parents. Consequently, the article emphasizes the necessity of supportive policies, strong collaborative efforts, and ongoing teacher training to address these issues. Ultimately, it underscores the importance of integrating Islamic teachings, multicultural values, and the principle of inclusiveness within religious education. Keywords : Inclusiveness, Tolerance, Islam, Teacher, Diversity.